Comportamento do consumidor: um estudo do mercado imobiliário em condomínios verticais fechados na região metropolitana de Natal - Campos Júnior, Geraldo Bezerra (2006)
The research in question looked for to establish the relation between the motivation (of the proprietor of apartment) to change itself of another one apartment, in closed vertical condominium (residential mobility) in the period of the recognition of the necessity, and the satisfaction with the apartment after consume. The universe or the population chosen for the development of the study was of proprietors of apartment in vertical condominiums located in the region metropolitan of Natal. The analysis of data was made using the techniques of linear regression and logistic regression between variables. The linear regression found relations between the motivations for housing change and the satisfaction in after consume with some attributes of the apartment. The logistic regression showed that relations between the motivations for change and the general satisfaction to the apartment exist as a whole, in the period after consumes. With regard to the motivation to change itself of a apartment for another one, some reasons shown more motivation them the others. The research found different degrees of satisfaction with certain characteristics of the apartment and degrees of no satisfaction with others. Finally the results of the research had contributed for the reply of the problem that guided the present study, therefore had obtained in such a way to find how much logistic not linear relations between the two periods purchase (recognition of the necessity and evaluation after consume) and had elucidated the process that goes since the choice the product until the satisfaction of the necessities